Development of a Bolometer Detector System for the NIST High Accuracy Infrared Spectrophotometer - Zong, Y. (J Res Natl Inst Stand Technol, 1998)
A bolometer detector system was developed for the high accuracy infrared spectrophotometer at the National Institute of Standards and Technology to provide maximum sensitivity, spatial uniformity, and linearity of response covering the entire infrared spectral range. The spatial response variation was measured to be within 0.1 %. The linearity of the detector output was measured over three decades of input power. After applying a simple correction procedure, the detector output was found to deviate less than 0.2 % from linear behavior over this range. The noise equivalent power (NEP) of the bolometer system was 6 × 10(−12) [Formula: see text] at the frequency of 80 Hz. The detector output 3 dB roll-off frequency was 200 Hz. The detector output was stable to within ± 0.05 % over a 15 min period. These results demonstrate that the bolometer detector system will serve as an excellent detector for the high accuracy infrared spectrophotometer.